2019
DOI: 10.1007/s40120-019-0143-2
|View full text |Cite
|
Sign up to set email alerts
|

Late Onset of Neuromyelitis Optica Spectrum Disorders

Abstract: IntroductionNeuromyelitis optica spectrum disorder (NMOSD) is an autoimmune demyelinating disease of the central nervous system. NMOSD starting after the age of 50 years is considered a “late onset” (LO-NMOSD) and seems to be particularly aggressive. The objective of this paper is to present a series of 37 Brazilian patients with LO-NMOSD.MethodsRetrospective data collection from medical records of patients with LO-NMOSD seen at 14 Brazilian specialized units.ResultsThe ratio of women to men in the sample was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…5,[7][8][9][10][11][12][13] In our LO-NMOSD-ON cohort, the mean age at ON onset was approximately 65 years, which was slightly higher than the ages reported in previous studies (56-59.4 years). 5,[7][8][9][10][11][12][13] However, the mean age at ON onset was 32.6 years in our EO-NMOSD-ON cohort, which is comparable with the typical age at NMOSD onset in previous studies (32-41 years). [2][3][4] Moreover, our previously published article, which studied prognostic factors for visual outcomes following the first episode of ON in each affected eye in overall age group of NMOSD-ON patients, showed that a median age at NMOSD-ON onset was 36 years (range 4-84 years).…”
Section: Demographic Datacontrasting
confidence: 71%
See 1 more Smart Citation
“…5,[7][8][9][10][11][12][13] In our LO-NMOSD-ON cohort, the mean age at ON onset was approximately 65 years, which was slightly higher than the ages reported in previous studies (56-59.4 years). 5,[7][8][9][10][11][12][13] However, the mean age at ON onset was 32.6 years in our EO-NMOSD-ON cohort, which is comparable with the typical age at NMOSD onset in previous studies (32-41 years). [2][3][4] Moreover, our previously published article, which studied prognostic factors for visual outcomes following the first episode of ON in each affected eye in overall age group of NMOSD-ON patients, showed that a median age at NMOSD-ON onset was 36 years (range 4-84 years).…”
Section: Demographic Datacontrasting
confidence: 71%
“…6 Few studies have investigated the epidemiological and clinical characteristics of LO-NMOSD. 5,[7][8][9][10][11][12][13] Some have compared these aspects with early-onset NMOSD (EO-NMOSD; age at NMOSD onset < 50 years). 5,[10][11][12][13] To the best of our knowledge, no studies have been performed to specifically compare clinical characteristics and long-term visual outcomes between patients with late-onset neuromyelitis optica spectrum disorder-related optic neuritis (LO-NMOSD-ON) and those with early-onset neuromyelitis optica spectrum disorder-related optic neuritis (EO-NMOSD-ON).…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study that studied late onset NMOSD utilized a total of 37 patients. Of the 37 patients analysed, 22 were whites and 15 were Africans (Fragoso et al, 2019). From the above discussed results, ethnic differences seem to be important in determining the age of onset.…”
Section: Age Of Onsetmentioning
confidence: 86%
“…Several studies have described the importance of the age at the onset of NMOSD; therefore, clinical differences might exist between late-onset (age at disease onset, >50 years) and early-onset NMOSD (age at disease onset, <50 years) NMOSD. Late-onset NMOSD may often be comorbid with age-related conditions compared with early-onset NMOSD [ 6 ]. Moreover, elderly patients have a tendency for a rapid worsening of their condition and poor response to immunomodulatory therapies [ 5 , 7 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In rare instances, NMOSD has been reported in elderly persons (over 50 years of age), and the clinical entity of late-onset NMOSD has been mentioned [ 3 ]. Compared with early-onset NNOSD (below 50 years of age), late-onset NMOSD may exhibit characteristic features, especially those associated with aging or other non-neurological issues [ 4 , 5 , 6 , 7 , 8 ]. Here, we report a case of very-late-onset NMOSD in an elderly patient (76 years of age) with breast cancer and Parkinson disease who exhibited an unusual disease course.…”
Section: Introductionmentioning
confidence: 99%